Relationship between service culture and quality perception in Chimborazo small and medium gastronomic enterprises - Vallejo Chávez, Luz Maribel; Arias Esparza, Jorge Enrique; Merino Chávez, Luis Gonzalo; Altamirano Capelo, Fernando Xavier (mktDESCUBRE; Vol 1 No 13 (2019): Thirteenth Edition - (January - June), 2019)
The quality of the service is a demand that customers demand in products and services, the research objective was to relate the culture of service and the perception of quality in SMEs of gastronomic services (restaurants), in the city of Riobamba, province of Chimborazo- Ecuador, 2017. The quantitative-qualitative approach, exploratory-descriptive level, documentary and field research, non-experimental-transversal design, the inductive-deductive, analytic-synthetic and systemic methods, the survey technique and the instrument a structured questionnaire for identify the service culture and customer quality perceptions. Two study samples were applied, the first 120 gastronomic SMEs, the second 398 clients. The results demonstrated a significant relationship between the Service Culture (CS) and the Perception of Service Quality (PCS). It was based on the SERVQUAL model, with 5 indicators (empathy, tangible elements, response capacity, safety and reliability), 32 items were evaluated, the reliability of the instrument with the Alpha-de-Cronbach (0,899), the Spearman Correlation ( r = 0,593) positive-moderate-strong relationship in the variables, later the gap analysis was applied with the following result: empathy (-1,67); tangible elements (-1,52); responsiveness (-1, 29); security (-1,20); reliability (-0,82). It is concluded that the results obtained propose improvement strategies to meet the demands, demands and needs of customers of gastronomic PYMEs.